The impact of incisional negative pressure wound therapy on the wound healing process after midline sternotomy - Rashed, Aref (Int Wound J, 2020)
Previous studies have reported that the use of incisional negative pressure wound therapy (INPWT) might reduce the incidence of wound infections, although its mechanism remains unknown. We designed a prospective study to explore the effects of INPWT on different stages of the wound healing process. After meeting the inclusion criteria, 108 patients were enrolled. Based on exclusion criteria four patients were excluded and 104 patients were randomised into two groups. INPWT was applied after primary closure of the midline sternotomy in the study group (n = 52), while conventional wound dressing was applied in the control group (n = 52). We documented the incidence of deep sternal wound infections and analysed the pre‐ and postoperative inflammatory biomarkers and scar size in both groups. No wound infections were observed in the study group compared with six cases (11.1%) in the control group, (P = .026). No significant differences were observed in the inflammatory biomarkers between the groups. Scar size was significantly smaller in the study group. We concluded that INPWT has less effect on the inflammatory phase and appears to have more effect on the proliferation phase through pronounced scar formation.